Analisis Partisipasi Masyarakat dalam Musrenbang Desa Menurut Prespektif Undang-Undang Nomor 6 Tahun 2014: Peran dan faktor penghambat serta pendorongpelaksanaan Musrenbang. - Puji Ana Sari; Saif Askari (Manabia: Journal of Constitutional Law, 2021)
This research is an attempt to explain the problem of the role of deliberation on development plans in absorbing the aspirations of the people of the Tangkil-Tengah Village, the implementation of the Musrenbang certainly has an effects on increasing village development. The formulation of the problem in this research is how the role Musrenbang in absorbing the aspirations of the village community and what are the supporting and inhibiting factors for the implementation of the Musrenbang. The purpose of the research is to find out the role of the Musrenbang in absorbing aspirations and what are supporting and inhibiting factors the Musrenbang. Type research is field research with qualitative approach. Technical analysis is a kualitative descriptive analysis technique.